Perceived Neighborhood Environment Impacts on Health Behavior, Multi-Dimensional Health, and Life Satisfaction - Liu, Jixiang; Yang, Linchuan; Xiao, Longzhu; Tao, Zhuolin (Frontiers in Public Health, 2022)
The impacts of perceived neighborhood environment on adults’ health and life satisfaction have drawn increasing academic attention. However, current studies usually examine multi-dimensional (physical, mental, perceived) health and life satisfaction separately, and few studies dealt with them simultaneously. Moreover, limited research has revealed the mechanisms behind the effects of perceived neighborhood environment on health and life satisfaction, as well as how such effects are moderated by socio-demographics. Therefore, employing the 2016 China Family Panel Study Dataset and using structural equation modeling, this study delves into the complicated relationships among perceived neighborhood environment, health behavior, health outcomes (i.e., body mass index, self-rated health status, and depression), and life satisfaction. Notably, it considers mediation and moderation simultaneously. It finds: 1) Better perceived neighborhood environment significantly promotes physical activity and reduces sedentary behavior, smoking, and drinking; 2) Health behavior fully mediates the effects of perceived neighborhood environment on health; 3) Perceived neighborhood environment significantly affects life satisfaction both directly and indirectly (through health behavior and health outcomes); 4) Socio-demographics moderate the above relationships. This study disentangles the complicated impacts of perceived neighborhood environment on adults’ multi-dimensional health and life satisfaction, thus providing policy makers and practitioners with nuancedknowledge for intervention.